Pemanfaatan Digital Marketing pada Produk UMKM di Masa Pandemi Covid-19 - Sunarmo Sunarmo; Nurlayla Tusubha; Ani Asriyah (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
One of the problems in marketing UMKM products is the lack of knowledge about digital marketing. This community service aims to provide education to UMKM players in RW 04 Kramat Pela Kebayoran Baru Jakarta Selatan about the use of digital marketing as a strategy to market UMKM products during the Covid-19 pandemic. The method used is bold socialization and video tutorials formed in a group. The result of this socialization is to inform how to create Instagram accounts, create logos with the Canva application and edit product photos, which are expected by UMKM players to be able to implement as a form of digital marketing strategy to increase sales turnover with a wider reach.